Implementation of Project-Based Learning Assisted by Interactive Flat Panel on Students' Learning Independence and Understanding of Mathematical Concepts - Hasanah, Nur; Gunawan (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examined the effect of Project-Based Learning assisted by Interactive Flat Panel on elementary students’ mathematical concept understanding and learning independence. The study was grounded in the need for mathematics instruction that supports conceptual construction, learner autonomy, and meaningful technology integration rather than procedural practice alone. A quantitative quasi-experimental design with a nonequivalent control group was employed. The participants were 24 elementary students divided into an experimental class and a control class, with 12 students in each group. The experimental class learned through Interactive Flat Panel-assisted Project-Based Learning, while the control class received comparison instruction without interactive technological support. Data were collected using a mathematical concept understanding test and a learning independence instrument. The analysis included descriptive statistics, Shapiro-Wilk normality testing, Levene’s homogeneity testing, independent samples t-test, Cohen’s d, and Pearson correlation. The results showed that the experimental class achieved higher mean scores than the control class in mathematical concept understanding (76.56 vs. 68.02) and learning independence (97.08 vs. 87.50). The t-test confirmed significant differences between groups for both variables, with a very large effect on concept understanding and a large effect on learning independence. Pearson correlation revealed a strong positive relationship between learning independence and mathematical concept understanding (r = .734, p = .007). These findings indicate that Interactive Flat Panel-assisted Project-Based Learning facilitates students’ conceptual reasoning while encouraging self-regulated learning behavior. The study contributes to technology-enhanced mathematics pedagogy by positioning interactive project-based instruction as an integrated approach for strengthening cognitive and self-regulatory learning outcomes in mathematics classrooms.